The Role of Oxidative Stress on the Pathogenesis of Graves' Disease. (10th December 2011) - Žarković Žarković, Miloš Miloš
Abstract : Graves' disease is a most common cause of hyperthyroidism. It is an autoimmune disease, and autoimmune process induces an inflammatory reaction, and reactive oxygen species (ROSs) are among its products. When balance between oxidants and antioxidants is disturbed, in favour of the oxidants it is termed "oxidative stress" (OS). Increased OS characterizes Graves' disease. It seems that the level of OS is increased in subjects with Graves' ophthalmopathy compared to the other subjects with Graves' disease. Among the other factors, OS is involved in proliferation of orbital fibroblasts. Polymorphism of the 8-oxoG DNA N-glycosylase 1 (hOGG1) involved in repair of the oxidative damaged DNA increases in the risk for developing Grave's disease. Treatment with glucocorticoids reduces levels of OS markers. A recent large clinical trial evaluated effect of selenium on mild Graves' ophthalmopathy. Selenium treatment was associated with an improved quality of life and less eye involvement and slowed the progression of Graves' orbitopathy, compared to placebo.